The bicentenary of Independence as a critical juncture of change in Central America and the contribution of development partners: the case of Spain - Caldentey-del Pozo, Pedro (2021)
The Bicentenary of the Central America independence matches with a critical juncture in the region, fuelled by internal and global factors. After forty years of inspiring national and regional development strategies, the plan derived from the Esquipulas Agreements has already delivered all it could. It has significantly improved the region's welfare, but it has broken neither dependence on special interests nor has it find solutions to the structural problems of the region, worsened by the Great recession and the pandemic. The regional framework seems to be once again the most appropriate place to define new consensus to challenge the crisis and face the future. Spain is a key partner of Central America and has a role to play in generating consensus and strengthening the regional dimension.